Helping students to read through I know why the Caged Bird Sings - Crespo Arízaga, Rosa
ABSTRACT This research project has been designed to develop students? reading and thinking competences through the major Autobiographical work of Maya Angelou: I Know Why the Caged Bird Sings. In this core knowledge unit, students will explore the impact of personal relationships on the author?s life. They will understand that characters undergo a transformation due to event in their lives, and how the environment plays a major role in human development. Students will also develop a sense of historical empathy by connecting personal experiences, information, insights and ideas with the experiences of others. Finally, students will determine and understand how the author?s or point of view affects the text. With the purpose of producing students who can use reading strategies to maximize their comprehension of the novel, I have provided authentic reading material for students to absorb vocabulary, and discourse structure as they occur in authentic contexts. Students thus will gain a more complete picture of the ways in which the elements of the language work together to convey meaning. They will also find that they can control their reading experiences, and they will gain confidence in their ability to read the new language